QUANTITATIVE DETERMINATION OF PERIODONTOPATHOGENS IN ELDERLY PATIENTS WITH ATHEROSCLEROSIS - Babenia, H.O.; Dienha, O.V.; Shnaider, S.A.; Nikolayeva, G.V.; Pochtar, V.M.; Korniichuk, O.E.; Lukovych, I.M. (World of Medicine and Biology, 2025)
Dental-plaque pathogens can translocate via the bloodstream, accumulate in atheromatous plaques of various arteries, or directly infect vascular endothelial cells, thereby taking an active part in the progression of atherosclerotic lesions. We performed a quantitative analysis of the “red-complex” periodontopathogens Porphyromonas gingivalis, Treponema denticola and Tannerella forsythia, as well as Aggregatibacter actinomycetemcomitans, Porphyromonas endodontalis, Prevotella intermedia and Fusobacterium nucleatum in gingival crevicular fluid. From every patient three to six of the targeted periodontopathogens were detected when a high-sensitivity threshold was applied. T. forsythia and F. nucleatum were identified in 100 % of samples, P. endodontalis in 77.8 %, P. gingivalis in 44.4 %, and T. denticola, A. actinomycetemcomitans and P. intermedia in 33.3 %. In all study participants, onset and/or progression of atherosclerosis may, to varying degrees, be attributable to the presence of large numbers of periodontopathogens in the oral cavity.
Keywords: atherosclerosis; generalised periodontitis; older age; periodontopathogens; polymerase chain reaction